The Role of Work Motivation in Mediating the Influence of Education and Training on the Performance of SLB Negeri 1 Badung Teachers - Faishal Luqman Prayitno; I Gusti Made Suwandana (Blantika: Multidisciplinary Journal, 2026)
Improving the quality of education for students with special needs largely depends on teachers’ competence and performance in carrying out their professional responsibilities. Special education teachers face more complex challenges because they must adapt learning methods to the characteristics and individual needs of students. One effort to improve teacher performance is through education and training programs; however, their effectiveness is also influenced by internal factors, such as work motivation. This study aims to analyze the effect of education and training on teacher performance and examine the role of work motivation as a mediating variable among teachers at SLB Negeri 1 Badung. This research employed a quantitative associative approach with a population and sample consisting of 34 teachers selected using a saturated sampling technique. Data were collected through questionnaires using a five-point Likert scale, observations, interviews, and documentation. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with the assistance of SmartPLS 4.0 software. The results indicate that education and training have a positive and significant effect on teacher performance; education and training positively influence work motivation; and work motivation significantly improves teacher performance. Furthermore, work motivation successfully mediates the relationship between education and training and teacher performance. This study concludes that improving the relevance and quality of teacher training programs, along with strengthening work motivation, is an essential strategy for continuously enhancing the performance of special education teachers